Effect of Dietary Energy Density on Increasing Blood Glucose Pattern and Hunger-Satiety Sensation - Ni Luh Putu Ayu Putri Sariningrat1, Purwo Sri Rejeki1, Irfiansyah Irwadi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: There was no data how these food density could effect on glucose and visual analog levels based on hunger-filled scales in Indonesian population. Objective To determine the effect of food energy density on glucose levels and hunger-satiety sensation. Material and Methods: Seventeen women 18-22 years of age with BMI> 25, were given low energy density breakfast (n = 9) and high energy density (n = 7). The subjects were fasted for 10 hours, fasting blood glucose levels was measured as well as hunger-satiety sensation with a visual analog scale (VAS), prior to treatment. Breakfast was started at 08.00 a.m chew up to 32 times for 15 minutes. Blood glucose levels and VAS measurement were taken back in 2 hours and 4 hours afterward. Result: There was a significant differences in glucose levels between 4 hours postpandrial and 2 hours postpandrial (p = 0.031) and also between 4 hours postpandrial and fasting state (p = 0.042) in both groups. Analysis of hunger level VAS (p = 0.02) and satiety level VAS (0.04) at 4 hours postpandrial also differ significantly. Correlation analysis between hunger level VAS and blood glucose was different significantly (p = 0.01) with r = -0.59. Conclusions: The low energy density foods produce a pattern of increasing blood glucose levels were more stable, thus, more able to suppress the sensation of hunger than high energy density.